The Innovation Paradox: Why Does Innovative Teacher Behavior Decrease Performance? - Nurdin Urbayani; Purwanto; Islah Gusmian; Abdul Bari Khan (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study examines the paradoxical relationship between innovative work behavior and teachers’ professional performance at Yayasan Al Abidin Surakarta. While innovation is commonly associated with improved performance, the findings reveal a very weak and negative correlation (r = –0.032; p = 0.643). Using a quantitative approach with Pearson correlation and linear regression, data were collected from 210 teachers through stratified random sampling. The analysis indicates that teachers’ innovative efforts do not automatically enhance professional performance, especially when not supported by institutional backing, clear evaluation systems, and organizational readiness for change. In such contexts, innovation may become an additional burden, potentially triggering stress, role conflict, and reduced work effectiveness. These findings suggest that innovation in educational settings must be viewed contextually. The assumption that every innovative action necessarily leads to constructive outcomes requires reconsideration. Instead, schools need to build an ecosystem that fosters new ideas, provides space for experimentation, and ensures alignment between innovation and institutional goals. Only then can innovative behavior make a meaningful contribution to teachers’ professional practices. This study contributes to the broader understanding of the complexity of innovation in education and highlights the importance of developing adaptive policies and management strategies. Such an approach can prevent innovation from becoming a source of disruption and instead position it as a driver for enhancing educational quality.